2013
DOI: 10.1016/j.sleep.2012.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes in REM sleep behavior disorder

Abstract: Objective REM sleep behavior disorder (RBD) is usually characterized by potentially injurious dream enactment behaviors (DEB). RBD treatment aims to reduce DEBs and prevent injury, but outcomes require further elucidation. We surveyed RBD patients to describe longitudinal treatment outcomes with melatonin and clonazepam. Methods We surveyed and reviewed records of consecutive RBD patients seen at Mayo Clinic between 2008–2010 to describe RBD-related injury frequency/severity as well as RBD Visual Analog Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
118
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(132 citation statements)
references
References 43 publications
6
118
0
4
Order By: Relevance
“…8 In a previous retrospective melatonin study and clonazepam, the visual analog scale (VAS), a simple and clear subjective scale, was used to evaluate treatment efficacy, was used by a bed partner or family member to evaluate RBD frequency and severity in daily life. 9 Similarly, in our present ramelteon study, the VAS was found to have utility in evaluating efficacy, with a trend toward significance. 6 The possible effects of gabapentin and pregabalin on RBD remain unknown: These pharmacological agents may modulate sleep stages (including REM sleep), suppress abnormal motor function directly, or affect dream contents via psychotropic properties.…”
supporting
confidence: 68%
“…8 In a previous retrospective melatonin study and clonazepam, the visual analog scale (VAS), a simple and clear subjective scale, was used to evaluate treatment efficacy, was used by a bed partner or family member to evaluate RBD frequency and severity in daily life. 9 Similarly, in our present ramelteon study, the VAS was found to have utility in evaluating efficacy, with a trend toward significance. 6 The possible effects of gabapentin and pregabalin on RBD remain unknown: These pharmacological agents may modulate sleep stages (including REM sleep), suppress abnormal motor function directly, or affect dream contents via psychotropic properties.…”
supporting
confidence: 68%
“…3 No randomized, double-blind, placebo-controlled study has been reported regarding treatment of RBD. However, a few drugs have been reported as effective, such as clonazepam, 4 melatonin, 5 and pramipexole, 6,7 a dopamine agonist. However, little is known regarding the relationship between RBD and dopaminergic deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin or clonazepam may be offered as therapies, with melatonin preferred to avoid exacerbating SDB and neurological dysfunction. 12 Taking a thorough medication history for any medications that could provoke or aggravate RSWA is important in all patients presenting with parasomnia behaviors. Several medications have been associated with RSWA, including tricyclic, selective serotonin reuptake inhibitors, and mixed mechanism antidepressants (i.e., mirtazapine and venlafaxine), and monamine oxidase inhibitors such as seligline.…”
Section: -4mentioning
confidence: 99%